2020
DOI: 10.1093/ofid/ofaa035
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Pilot Study of Cyclophosphamide as an Adjunct Treatment in Patients With Adult-Onset Immunodeficiency Associated With Anti-interferon-γ Autoantibodies

Abstract: Background Adult-onset immunodeficiency associated with interferon-γ autoantibody (IGA) is an emerging disease. The majority of patients require both antimicrobial and immunosuppressive treatments. However, anti-CD20 therapy is not fully accessible in a resource-limited setting to date. Background The objectives of this work were to study the efficacy of cyclophosphamide treatment and the role of laboratory biomarkers for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…However, one study reported a significant improvement in clinical symptoms after plasma exchange therapy [ 10 ]. Supplementation of IFN-γ recombinant protein [ 34 ], cyclophosphamide [ 35 , 36 ] and B cell depletion with an anti-CD20 antibody [ 37 , 38 ] have also been successfully used as adjuvant therapies in combination with antimicrobial therapy in a small number of patients. Prospective randomized clinical trials are needed to determine the therapeutic efficiency of these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported a significant improvement in clinical symptoms after plasma exchange therapy [ 10 ]. Supplementation of IFN-γ recombinant protein [ 34 ], cyclophosphamide [ 35 , 36 ] and B cell depletion with an anti-CD20 antibody [ 37 , 38 ] have also been successfully used as adjuvant therapies in combination with antimicrobial therapy in a small number of patients. Prospective randomized clinical trials are needed to determine the therapeutic efficiency of these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, patients showing progressive or relapsed infections despite at least a 3-month or over 1-year course of intensive antimicrobial therapy were treated with rituximab, and favorable clinical outcomes were achieved. 10 , 11 Our patient had a severe infection and had no significant benefit from antibiotic treatment. We are unsure whether this immunosuppressive drug benefitted the patient or exacerbated the infection.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have reported that immunosuppressive agents such as anti-CD20 monoclonal antibodies and cyclophosphamide can effectively reduce AIGA titers and have achieved favorable clinical outcomes in patients with refractory NTM infections. 22 , 23 However, the detection of AIGAs in the patient serum was not considered until March 2016, when the patient was finally confirmed to have high titers of AIGAs. Furthermore, the patient showed a good response to anti-NTM therapy in 2016, so she did not receive immunotherapy for AIGAs throughout the clinical course.…”
Section: Discussionmentioning
confidence: 99%